Detecting Tidal Flood Pattern with Landsat TM Remote Sensing Data in South Sumatra Coastal Area - KUSUMO NUGROHO; U.S WIRADISASTRA; S. ARSYAD; HIDAYAT PAWITAN; . SUDARSONO (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2007)
Detecting the availability of sufficient water in tidal land management is important for agriculture. Tidal flood pattern provides an information of area where has tidal flood as well as drought by time and places. The objectives of this research are 1) to study the tidal flood spatial pattern by using real time data and digital data image processing, 2) to determine a tidal flood classification based on ground water level on a specific locationand time, and 3) to study the hydrological factors affecting the flood. The tidal flood pattern can be classified within a block by their ground water fluctuation. The visual analysis with four image of different time, gives a clear differences between tidal flood pattern change and tidal fluctuation. The classification on the moist Landsat TM image after a Tesseled Cap transformation can produce classified image with similar flooded condition with the same range of ground water level. After the test, the tidalflooded pattern was found similar with the classification results. The tidal flood pattern is also recognized having a specific relationship with land use or land utilization type. The land use and land management affect the pattern. The application of geographical information system, especially remote sensing digital image data analysis, will help in determining tidal flood pattern as well as the ground water spatial pattern.